Metabolic engineering of Yarrowia lipolytica for scutellarin production - Yina Wang; Xiaonan Liu; Bihuan Chen; Wei Liu; Zhaokuan Guo; Xiangyu Liu; Xiaoxi Zhu; Jiayu Liu; Jin Zhang; Jing Li; Lei Zhang; Yadi Gao; et al. (Synthetic and Systems Biotechnology, 2022)
Scutellarin related drugs have superior therapeutic effects on cerebrovascular and cardiovascular diseases. Here, an optimal biosynthetic pathway for scutellarin was constructed in Yarrowia lipolytica platform due to its excellent metabolic potential. By integrating multi-copies of core genes from different species, the production of scutellarin was increased from 15.11 mg/L to 94.79 mg/L and the ratio of scutellarin to the main by-product was improved about 110-fold in flask condition. Finally, the production of scutellarin was improved 23-fold and reached to 346 mg/L in fed-batch bioreactor, which was the highest reported titer for de novo production of scutellarin in microbes. Our results represent a solid basis for further production of natural products on unconventional yeasts and have a potential of industrial implementation.